(untitled) (Texas Journal of Philology, Culture and History, 2023)
The article aims to raise public opinion about the emergence of the Uzbek press and its coverage of all aspects of society’s social-political, economic production, and cultural-spiritual life, exposing and criticizing the shortcomings, defects, and social evils found in these areas. In particular, the originality of satirical journalism, which follows the laws of social laughter - satire and humor, in reflecting reality and influencing it is analyzed